Advanced small cell carcinoma of the cervix - Successful treatment with concurrent etoposide and cisplatin chemotherapy and extended field radiation: A case report and discussion - Amishi Bajaj; Mahesh Gopalakrishnan; Matthew M. Harkenrider; John R. Lurain; William Small, Jr (Elsevier, 2018)
The purpose of this article is to present a case of successful treatment of a patient with stage IVB small cell carcinoma of the cervix (SCCC) who was treated with concurrent chemoradiotherapy (CCRT) consisting of etoposide/cisplatin (EP) chemotherapy, external beam radiation therapy (EBRT), and brachytherapy. The patient has since remained without evidence of disease for nearly six years. This report reviews and summarizes the existing case literature on SCCC.